Target specific post-harvest treatment by gamma radiation for the microbial safety of dried Melissa officinalis and Aloysia citrodora - Meneses, Márcia (2018)
This study aimed to assess a specific gamma radiation dose to be applied as a post-harvest process to guarantee the microbial safety of two medicinal plants, Melissa officinalis and Aloysia citrodora. Dried plants treated with gamma radiation indicated that a dose of 5 kGy could be applied as a post-harvest treatment process of M. officinalis and A. citrodora, assuring the microbial safety of dried medicinal plants and lowering the potentiality of deleterious effects on plants’ quality attributes. This will enhance the safety and quality of the dried plants to be used as raw materials in industrial applications.